2020
DOI: 10.1055/s-0041-1726140
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and Outcomes with First-Line Chemotherapy in Advanced Cholangiocarcinomas—A Relatively Rare Component of Biliary Tract Cancers in India

Abstract: Background Biliary tract cancers (BTCs) are a rare group of cancers with limited data with respect to advanced unresectable cholangiocarcinoma (CCA). Materials and Methods The study is a retrospective study of patients with advanced unresectable/metastatic CCA, who received first-line palliative chemotherapy (CT1) from January 2014 to March 2019 at the Tata Memorial Hospital, Mumbai. Baseline clinical characteristics, chemotherapeutic regimens, and toxicities were evaluated. Results One hundred and forty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…15 16 This could be due to differences in the tumor biology at these two sites. The CCA cohort of ours had a median OS of 9 months, which was inferior to that reported by Bhargava et al 23 (12 months), ABC-02 trial (11.7 months), and BT22 trial (11.2 months).…”
Section: Discussioncontrasting
confidence: 88%
“…15 16 This could be due to differences in the tumor biology at these two sites. The CCA cohort of ours had a median OS of 9 months, which was inferior to that reported by Bhargava et al 23 (12 months), ABC-02 trial (11.7 months), and BT22 trial (11.2 months).…”
Section: Discussioncontrasting
confidence: 88%
“… 1 Advanced BTCs are often refractory to chemotherapy, and the response rate for first‐line chemotherapy combining gemcitabine and cisplatin is only about 25%–30%, with a median overall survival (OS) of 11–13 months. 2 , 3 The efficacy of second‐line chemotherapy for BTCs remains dismal. The ABC‐06 study showed that combination therapy of leucovorin, fluorouracil, and oxaliplatin (FOLFOX) only achieved an objective response rate (ORR) of 5% and an OS of 6.2 months, 4 and the NIFTY study reported that liposomal irinotecan in combination with 5‐fluorouracil/leucovorin achieved a median OS of 8.6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Late diagnosis, a high relapse rate after surgery, and refractoriness to treatments contribute to poor prognosis in patients with BTCs, with a 5 year survival rate below 20% 1. Advanced BTCs are often refractory to chemotherapy, and the response rate for first‐line chemotherapy combining gemcitabine and cisplatin is only about 25%–30%, with a median overall survival (OS) of 11–13 months 2,3. The efficacy of second‐line chemotherapy for BTCs remains dismal.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis done by Valle et al further supported this treatment strategy 12. In a recent large retrospective study on cholangiocarcinomas to evaluate outcomes with first-line chemotherapy by Bhargava et al , the median PFS was 7.56 months and overall survival (OS) was 12.16 months with GemCis regimen being used in 63.5% of patients 13. These findings are very similar to those seen in the seminal ABC-02 (median PFS—8 months; median OS—11.7 months) and BT22 (median PFS—5.8 months; median OS—11.2 months) Studies.…”
Section: Discussionmentioning
confidence: 98%